IMPROVING PJOK LEARNING OUTCOMES USING DIGITAL FLIPBOOK IN CLASS X - Hadi Suhendro; Aunurrahman; Indri Astuti (Jurnal Scientia, 2022)
The purpose of this study is to improve learning outcomes of class X PJOK. This research method uses classroom action research with a total of 22 students. From the learning outcomes at the initial meeting, the class average reached 67, in the first cycle the class average reached 74 and continued with the second cycle with the class average reaching 88. Thus, this digital book can be categorized as "GOOD" for used.